Obywatelskość w edukacji humanistycznej (w duchu Hannah Arendt) - Koc, Krzysztof (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
The author analyses Hannah Arendt’s writings in search of inspirations for reflecting on the contemporary world’s problems in humanistic (school) education, finding such inspirations in the topics that interested the author of The Human Condition and in her perception of politics, citizenship and thinking as such. Koc’s thesis is that educational documents show a clear deficit of reflection on current challenges, often transnational, that need to be analysed from multiple angles. The article emphasises Arendt’s warnings about non-thinking as an attitude conducive to totalitarianism, which should unsettle anyone interested in the concept of educating young people. Reconstructing Arendt’s axiology of citizenship and emphasising the value of journalistic texts as stories that uncover ambiguity and ask key questions, the author calls for a reconsideration of the nature of Polish language education in contemporary school.